Significant power enhancement of magneto-mechano-electric generators by magnetic flux concentration. Issue 11 (2nd October 2020) - Song, Hyunseok; Patil, Deepak Rajaram; Yoon, Woon-Ha; Kim, Kwang-Ho; Choi, Cheol; Kim, Jong-Hyun; Hwang, Geon-Tae; Jeong, Dae-Yong; Ryu, Jungho
Abstract : A magneto-mechano-electric (MME) generator comprising a magnetoelectric (ME) composite and magnetic flux concentrator (MFC) can effectively harvest the tiny magnetic noise to power the autonomous internet of things (IoT) sensor networks. Abstract : A magneto-mechano-electric (MME) generator comprising a cantilever structured magnetoelectric (ME) composite having a magnet-proof mass is an ideal candidate for powering autonomous Internet of Things (IoT) sensor networks by scavenging electric energy from ambient magnetic noise. However, charging an energy storage device in a short time using an MME generator from low-intensity magnetic noise flux spreading in radial directions, e.g., around power cables, requires the generator volume to be enlarged. Here, we demonstrated a novel method to enhance the output power of the given MME generator by concentrating a magnetic flux around the circumference of an MME generator structure using a magnetic flux concentrator (MFC) fabricated from a high-permeability magnetic material. The output power of the MME generator was significantly enhanced by optimizing the MFC structure in terms of its shape, aspect ratio, magnetic permeability, and the number of layers, both through finite element analysis and experiments. The MME generator with the MFC was observed to generate a maximum power of 3.33 mW, which was 285% of that of the condition without the MFC (1.17 mW) under a weak magnetic field of 8 Oe (= 8 G = 800 μT in air), which was sufficient to charge the 2.2 mF storage capacitor within 13 s and continuously operate an IoT sensor for a long period. The stored energy is also sufficient enough to turn on 100 blue LEDs with high intensity. Furthermore, we demonstrated a realistic practical application by installing the self-powered wireless environmental monitoring module consisting of the MME generator with the MFC at a power substation, which successfully scavenges the power from the magnetic fields around the power cables and continuously operates a temperature wireless sensor. These results indicated that the MFC has great potential to enhance the performance of an MME generator as the power source of standalone IoT sensors without enlarging the MME generator.